A high-throughput liquid bead array assay confirms strong correlation between SARS-CoV-2 antibody level and COVID-19 severity - Bennett, Monique; Yoder, Sandra; Brady, Eric; Pulley, Jill M.; Rhoads, Jillian P.; Stewart, Thomas G.; Bernard, Gordon R.; Creech, C. Buddy; Wheeler, Allison P.; Thomsen, Isaac (iScience, 2021)
A detailed understanding of the adaptive host response to SARS-CoV-2 infection in humans is urgently needed. We developed a sensitive, high-throughput, and efficient assay using liquid bead array technology. We observed advantages over traditional ELISA for the detection and quantification of binding IgG against the receptor binding domain (RBD) of SARS-CoV-2. To determine whether COVID-19 symptom severity correlates with SARS-CoV-2 IgG, we measured anti-RBD IgG levels from 67 subjects recovered from PCR-confirmed COVID-19. We found that COVID-19 symptom severity strongly correlated with RBD IgG level (p < 0.001). These findings have substantial implications for public policy surrounding assessments of antibody responses and possible immunity, as not all cases of COVID-19 can be assumed to generate a protective antibody response, and mild disease in particular is capable of generating very low-level anti-RBD IgG levels. These findings also have important implications for the selection of donors for convalescent plasma to be used therapeutically. [Display omitted] •We developed a sensitive, high-throughput assay for quantification of SARS-CoV-2 IgG•The assay uses liquid bead array technology for efficient and reproducible results•COVID-19 symptom severity was strongly correlated with SARS-CoV-2 SRBD IgG levels Biological Sciences; Microbiology; Virology; Viral Microbiology